Secondary battery and electric device
By using a structure-specific combination of first and second carbon-based materials in the negative electrode sheet of the secondary battery, the problem that the secondary battery is difficult to take into account both the cycle performance and the kinetic performance under high energy density is solved, and excellent battery performance is achieved.
Patent Information
- Application Number
- CN202311641330.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult for existing secondary batteries to take into account excellent cycling and dynamic performance while having high energy density.
By using a negative electrode active material, including a first carbon-based material and a second carbon-based material, the outer region structure of the first carbon-based material is denser than the inner region and has a high degree of graphitization, the second carbon-based material has a low degree of graphitization and a large layer spacing.
The high energy density, excellent cycling performance and kinetic performance of the secondary battery are achieved, which reduces the occurrence of side reactions and improves the transmission speed of active ions.
Smart Images

Figure CN119852480A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As the application scope of secondary batteries becomes wider and wider, people have also put forward higher requirements for their performance.
[0003] Therefore, how to make secondary batteries have high energy density and excellent cycle performance and kinetic performance has become an urgent problem to be solved in the field. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery and an electric device, wherein the secondary battery has high energy density while achieving excellent cycle performance and dynamic performance.
[0005] In a first aspect, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and comprising a negative electrode active material. The negative electrode active material comprises a first carbon-based material and a second carbon-based material, the first carbon-based material comprising an external region and an internal region located inside the external region, the external region refers to a region extending from the particle surface of the first carbon-based material to the inside of the particle by a distance of 2.5 μm, in a cross-sectional view of the first carbon-based material, the total pore area of the external region is recorded as S1, the total pore area of the internal region is recorded as S2, and S2>S1, and the graphitization degree of the first carbon-based material is greater than the graphitization degree of the second carbon-based material.
[0006] By making the negative electrode active material in the negative electrode film layer include a first carbon-based material and a second carbon-based material at the same time, wherein S2>S1 of the first carbon-based material, it means that the structure of the outer region of the carbon-based material is denser than that of the inner region, and the degree of graphitization of the first carbon-based material is greater than that of the second carbon-based material. Thus, the negative electrode plate can have a high compaction density, low volume change performance and high active ion transmission speed, so that the secondary battery using the negative electrode plate can have high energy density while taking into account excellent cycle performance and kinetic performance.
[0007] In some embodiments, the graphitization degree of the first carbon-based material is greater than or equal to 95.5%, and can be 95.5%-98.0%; the graphitization degree of the second carbon-based material is 85%-90.5%, and can be 85.5%-90%. By making the graphitization degree of the first carbon-based material within the above range, it is beneficial for the negative electrode active material to have a high compaction density, and by making the graphitization degree of the second carbon-based material within the above range, it is beneficial to improve the active ion transport performance of the negative electrode film layer, so that the secondary battery can have both high energy density and good kinetic performance.
[0008] In some embodiments, the gram capacity of the second carbon-based material is less than the gram capacity of the first carbon-based material. By combining the first carbon-based material with a high capacity with the second carbon-based material with a low degree of graphitization, it is beneficial for the secondary battery to have both high energy density and good kinetic performance.
[0009] In some embodiments, the interlayer spacing of the 002 crystal plane of the second carbon-based material is greater than the interlayer spacing of the 002 crystal plane of the first carbon-based material. The interlayer spacing of the second carbon-based material is larger, which is conducive to the rapid deintercalation of active ions, and the interlayer spacing of the first carbon-based material is smaller, thereby having a higher gram capacity. Therefore, by adjusting the interlayer spacing of the 002 crystal plane of the second carbon-based material to be greater than the interlayer spacing of the 002 crystal plane of the first carbon-based material, it is beneficial for the secondary battery to have both high energy density and good kinetic performance.
[0010] In some embodiments, the second carbon-based material D / I G Greater than the I of the first carbon-based material D / I G , I D The Raman spectrum of carbon-based materials is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of carbon-based materials is 1580±50cm -1 G peak intensity at, optionally, the I D / I G Denoted as A, I of the second carbon-based material D / I G By adjusting the I of the second carbon-based material D / I G Greater than the I of the first carbon-based material D / I G On the one hand, it is beneficial to improve the overall surface stability of the negative electrode active material, reduce the occurrence of side reactions, and improve the cycle performance; on the other hand, it is also beneficial for the secondary battery to have good kinetic performance.
[0011] In some embodiments, the first carbon-based material and / or the second carbon-based material include primary particles. Optionally, the number of the primary particles in the first carbon-based material accounts for greater than or equal to 80%, and the number of the primary particles in the second carbon-based material accounts for greater than or equal to 80%. By making the first carbon-based material and / or the second carbon-based material contain an appropriate proportion of primary particles, it can have a higher structural stability and reduce the occurrence of side reactions, thereby improving the cycle performance of the secondary battery; in addition, the compaction density of the negative electrode film layer can also be increased, thereby improving the energy density of the secondary battery.
[0012] In some embodiments, 1.8≤S2 / S1≤199.8, 2.3≤S2 / S1≤148.7. Thus, the secondary battery can better balance the dynamic performance and the cycle performance.
[0013] In some embodiments, the area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 By controlling the area of the pore structure in the outer region of the first carbon-based material within the above range, the outer region of the first carbon-based material can have a dense structure, thereby effectively improving the structural stability of the first carbon-based material and avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, thereby effectively improving the cycle performance of the secondary battery.
[0014] In some embodiments, the inner region of the first carbon-based material includes one or more areas greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of 0.15 μm 2 -2.0μm 2 By making the internal area of the first carbon-based material include the pore structure of the above size, on the one hand, sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, reducing the risk of breakage of the first carbon-based material particles and reducing the occurrence of side reactions; on the other hand, the compaction density of the negative electrode film layer can be increased to buffer the volume change of the negative electrode film layer.
[0015] In some embodiments, at least part of the surface of the first carbon-based material has a coating layer. Optionally, the coating layer includes a carbon coating layer. This is beneficial to improve the dynamic performance of the secondary battery.
[0016] In some embodiments, the gram capacity of the first carbon-based material is greater than or equal to 355 mAh / g, and can be 355 mAh / g-370 mAh / g. When the gram capacity of the first carbon-based material is within the above range, it is beneficial to improve the energy density of the secondary battery.
[0017] In some embodiments, the true density of the first carbon-based material is 2.22 g / cm 3 -2.27g / cm 3 , optional 2.23g / cm 3 -2.26g / cm 3 When the true density of the first carbon-based material is within the above range, it is beneficial to improve the compaction density of the negative electrode film layer and improve the energy density of the secondary battery.
[0018] In some embodiments, the first carbon-based material has a powder compaction density of 1.65 g / cm2 at a pressure of 20,000 N. 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3 By making the compaction density of the powder of the first carbon-based material within the above range, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery.
[0019] In some embodiments, the volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and can be 10.0 μm-22.0 μm. In some embodiments, the volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-45.0 μm, and can be 16.5 μm-42.0 μm.
[0020] By making the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material within the above range, it is beneficial to improve the transmission performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. It can also reduce the occurrence of side reactions and improve the cycle performance of the secondary battery.
[0021] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is less than or equal to 1.55, and can be selected as 0.90-1.50. By making the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material within the above range, its particle stacking performance is good, which is conducive to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also conducive to adjusting the pore distribution of the negative electrode film layer, improving the active ion and electron transport performance, and improving the infiltration and retention characteristics of the negative electrode film layer to the electrolyte, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0022] In some embodiments, the tap density of the first carbon-based material is 0.85 g / cm 3 -1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm3 By making the tap density of the first carbon-based material within the above range, the carbon material has good processing performance, which can increase the compaction density of the negative electrode film layer and improve the energy density of the secondary battery.
[0023] In some embodiments, the first carbon-based material D / I G Less than or equal to 0.280, and can be 0.155-0.220. Thus, the active lithium consumption can be effectively reduced, the cycle performance can be further improved, and the kinetic performance can be taken into consideration at the same time.
[0024] In some embodiments, the adsorption amount of linseed oil by 100g of the first carbon-based material is 30mL-47mL. When the adsorption amount of linseed oil by the carbon material is within the above range, the processing performance of the first carbon-based material is good, and the surface side reaction activity of the particles is low, thereby reducing the consumption of active ions by SEI film formation.
[0025] In some embodiments, the gram capacity of the second carbon-based material is 280 mAh / g-340 mAh / g, and can be 300 mAh / g-338 mAh / g. By adjusting the gram capacity of the second carbon-based material within the above range, the dynamic performance of the secondary battery can be improved.
[0026] In some embodiments, the interlayer spacing of the second carbon-based material 002 crystal plane is 0.33622nm-0.33669nm, and can be 0.33626nm-0.33665nm. By adjusting the interlayer spacing of the second carbon-based material within the above range, it is beneficial to the rapid deintercalation of active ions, thereby improving the active ion transport performance of the negative electrode film layer so that the secondary battery can have good kinetic performance.
[0027] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 10 μm-18 μm, and can be optionally 12 μm-17 μm. By making the volume distribution particle size Dv50 of the second carbon-based material within the above range, the specific surface area of the second carbon-based material can be reduced, the occurrence of side reactions can be reduced, and the cycle performance of the secondary battery can be improved.
[0028] In some embodiments, the tap density of the second carbon-based material is 0.95 g / cm 3 -1.35g / cm 3 , optional 1.00g / cm 3 -1.30g / cm 3 By making the tap density of the second carbon-based material within the above range, the processing performance of the second carbon-based material is better.
[0029] In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is 25.0 μm-45.0 μm, and can be 26.5 μm-42.0 μm. The second carbon-based material has good processing performance and is conducive to having a suitable pore distribution in the negative electrode film layer, thereby improving the dynamic performance of the secondary battery.
[0030] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is less than or equal to 1.90, and can be selected as 0.90-1.85. This is beneficial to improving the compaction density of the negative electrode film layer and the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transmission performance in the negative electrode film layer, and thus improve the kinetic performance of the secondary battery.
[0031] In some embodiments, the adsorption amount of linseed oil by 100g of the second carbon-based material is 38mL-50mL. When the adsorption amount of linseed oil by the carbon material is within the above range, the processing performance of the second carbon-based material particles is good, and the surface side reaction activity is low, thereby reducing the consumption of active ions by SEI film formation.
[0032] In some embodiments, the second carbon-based material is artificial graphite. Artificial graphite has a stable structure, thereby improving the cycle performance of the secondary battery.
[0033] In some embodiments, the second carbon-based material D / I G The ratio is 0.20-0.40, and can be 0.25-0.35, thereby further improving the dynamic performance.
[0034] In some embodiments, the content of the first carbon-based material in the negative electrode active material is greater than or equal to 30wt%, and can be 50wt%-80wt%. When the content of the first carbon-based material is within the above range, the secondary battery has high energy density and good kinetic performance and cycle performance.
[0035] In some embodiments, the negative electrode active material further comprises a silicon-based material, and optionally, in the negative electrode active material, the content of the silicon-based material is 0.5wt%-30wt%. The higher lithium insertion potential of the silicon-based material helps to improve the kinetic performance of the secondary battery; at the same time, it can also improve the negative electrode capacity, thereby further improving the energy density of the secondary battery.
[0036] In some embodiments, the compaction density of the negative electrode film layer is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3-1.85g / cm 3 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good cycle performance and kinetic performance.
[0037] In some embodiments, the surface density of the negative electrode film layer is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good cycle performance and kinetic performance.
[0038] In some embodiments, the thickness of the negative electrode film layer is 40 μm-120 μm, and optionally 45 μm-100 μm.
[0039] A second aspect of the present application provides an electrical device, which includes the secondary battery of the first aspect of the present application.
[0040] Effects of the Invention
[0041] The secondary battery of the present application has high energy density and excellent cycle performance and kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0043] Figure 1 A schematic diagram of a cross-sectional image of a particle of the first carbon-based material of the present application.
[0044] Figure 2 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0045] Figure 3 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.
[0046] Figure 4 It is a schematic diagram of an embodiment of a battery module of the present application.
[0047] Figure 5 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0048] Figure 6 yes Figure 5 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0049] Figure 7 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0050] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate, 100 first carbon-based material, 101 external area, 102 internal area. DETAILED DESCRIPTION
[0051] Below, the embodiments of the secondary battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0056] At present, in secondary batteries, carbon-based materials are mostly used as negative electrode active materials. In order to improve the performance of negative electrode active materials, carbon-based material particles are usually treated by surface coating. However, the above methods lead to a decrease in both gram capacity and compaction density, affecting the energy density of secondary batteries. The surface coating layer is usually a soft or hard carbon material, which has high activity and many side reactions, affecting the cycle performance of secondary batteries.
[0057] Therefore, it is difficult for current secondary batteries to have both high energy density and good kinetic and cycle performance.
[0058] In view of this, a first aspect of the embodiments of the present application provides a secondary battery.
[0059] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.
[0060] [Negative electrode]
[0061] In the secondary battery of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and including a negative electrode active material. The negative electrode active material includes a first carbon-based material and a second carbon-based material, the first carbon-based material includes an external region and an internal region located inside the external region, the external region refers to a region extending from the particle surface of the first carbon-based material to the inside of the particle by a distance of 2.5 μm, in the cross-sectional view of the first carbon-based material, the total pore area of the external region is recorded as S1, the total pore area of the internal region is recorded as S2, and S2>S1, and the graphitization degree of the first carbon-based material is greater than the graphitization degree of the second carbon-based material.
[0062] In the present application, "inner region" refers to a region other than an outer region in a material particle.
[0063] By making the first carbon-based material satisfy S2>S1, the first carbon-based material has the following characteristics: the number of pores in the inner region is large and / or the pore size is large, while the number of pores in the outer region is small and / or the pore size is small, indicating that the structure of the outer region of the carbon-based material is denser than the inner region. The pore structure in the inner region of the first carbon-based material can reserve the required expansion space for the change in particle volume, thereby reducing the risk of particle crushing to produce a new interface, reducing the rebound rate of the thickness of the negative electrode film layer, and thus reducing the occurrence of side reactions; the number of pores in the outer region of the first carbon-based material is small and / or the pore size is small, thereby making the first carbon-based material particles have a stable structure and avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, thereby further reducing the occurrence of side reactions and reducing the consumption of active ions by the SEI film formation inside the particles. Therefore, by including the above-mentioned first carbon-based material, the cycle performance of the secondary battery can be improved.
[0064] In the present application, the second carbon-based material has a lower degree of graphitization than the first carbon-based material, and has a larger interlayer spacing, which is conducive to the rapid deintercalation of active ions and has good kinetic performance. However, the gram capacity and compaction density of the second carbon-based material are low, which has an adverse effect on the energy density of the negative electrode film layer and even the secondary battery. The first carbon-based material has a high gram capacity and a porous structure, and its compaction density is relatively large. Therefore, it can improve the energy density of the negative electrode film layer and even the secondary battery.
[0065] In the present application, by making the negative electrode active material in the negative electrode film layer include the above-mentioned first carbon-based material and the second carbon-based material at the same time, the high capacity and high compaction density characteristics of the first carbon-based material and the excellent kinetic characteristics of the second carbon-based material can be fully utilized, so that the secondary battery has high energy density and excellent kinetic performance. In addition, as mentioned above, the internal pore structure of the first carbon-based material can buffer the expansion of particles when lithium is embedded, while the second carbon-based material has a low degree of graphitization and a large interlayer spacing, and the volume change of the particles is small when lithium ions are embedded, and the expansion is low, that is, both the first carbon-based material and the second carbon-based material can reduce expansion, thereby effectively avoiding SEI damage caused by expansion, significantly reducing active lithium consumption, and greatly improving the cycle performance of the battery.
[0066] In some embodiments, the degree of graphitization of the first carbon-based material is greater than or equal to 95.5%, and can be selected from 95.5% to 98.0%. By adjusting the degree of graphitization of the first carbon-based material within the above range, it is beneficial for the negative electrode active material to have a high compaction density and gram capacity. The degree of graphitization of the second carbon-based material is 85% to 90.5%, and can be selected from 85.5% to 90%. By making the degree of graphitization of the second carbon-based material within the above range, at this time, the interlayer spacing of the second carbon-based material is large, thereby improving the active ion transport performance of the negative electrode film layer, thereby, by simultaneously containing the first carbon-based material and the second carbon-based material, the secondary battery can take into account both high energy density and good kinetic performance. In some embodiments, the gram capacity of the second carbon-based material is less than the gram capacity of the first carbon-based material. Optionally, the gram capacity of the first carbon-based material is greater than or equal to 355mAh / g, and can be selected from 355mAh / g to 370mAh / g. When the gram capacity of the first carbon-based material is within the above range, it is beneficial to improve the energy density of the secondary battery. Optionally, the gram capacity of the second carbon-based material is 280mAh / g-340mAh / g, and optionally 300mAh / g-338mAh / g. Thus, by combining the first carbon-based material with a high capacity with the second carbon-based material with a low degree of graphitization, it is beneficial for the secondary battery to have both high energy density and good kinetic performance.
[0067] In some embodiments, the interlayer spacing of the 002 crystal plane of the second carbon-based material is greater than the interlayer spacing of the 002 crystal plane of the first carbon-based material. The interlayer spacing of the second carbon-based material is larger, which is conducive to the rapid deintercalation of active ions, and the interlayer spacing of the first carbon-based material is smaller, thereby having a higher specific capacity. Therefore, by adjusting the interlayer spacing of the 002 crystal plane of the second carbon-based material to be greater than the interlayer spacing of the 002 crystal plane of the first carbon-based material, the secondary battery is further improved to have both high energy density and good kinetic performance.
[0068] In some embodiments, the second carbon-based material D / I GGreater than the I of the first carbon-based material D / I G , I D The Raman spectrum of carbon-based materials is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of carbon-based materials is 1580±50cm -1 Optionally, the I of the first carbon-based material D / I G Denoted as A, I of the second carbon-based material D / I G The ratio of A / B is 0.45-0.85. For example, it can be 0.46, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.8, 0.85. D / I G Greater than the I of the first carbon-based material D / I G On the one hand, it is beneficial to improve the overall surface stability of the negative electrode active material, reduce the occurrence of side reactions, and improve the cycle performance; on the other hand, it is also beneficial for the secondary battery to have good kinetic performance.
[0069] In some embodiments, the first carbon-based material and / or the second carbon-based material include primary particles. Optionally, the amount of the primary particles in the first carbon-based material is greater than or equal to 80%, for example, it can be 80%-100%, 85%-90%, 90%-100%, 95%-100%, or 85%-100%. The amount of the primary particles in the second carbon-based material is greater than or equal to 80%, for example, it can be 80%-100%, 85%-90%, 90%-100%, 95%-100%, or 85%-100%. By making the first carbon-based material and / or the second carbon-based material contain an appropriate proportion of primary particles, it can have a higher structural stability and reduce the occurrence of side reactions, thereby improving the cycle performance of the secondary battery; in addition, the compaction density of the negative electrode film layer can also be increased, further improving the energy density of the secondary battery.
[0070] In some embodiments, preferably 1.8≤S2 / S1≤199.8, for example, 2≤S2 / S1≤199.8, 2≤S2 / S1≤190, 2.3≤S2 / S1≤180, 2.3≤S2 / S1≤170, more preferably 2.3≤S2 / S1≤148.7, for example, 3.0≤S2 / S1≤140, 4.0≤S2 / S1≤100. The inventors found in further research that when S2 / S1 is also within the above range, the secondary battery can better balance good kinetic performance and good cycle performance.
[0071] In the present application, the total pore area S1 of the outer region and the total pore area S2 of the inner region of the first carbon-based material can be obtained by testing the cross-sectional image of the first carbon-based material.
[0072] Figure 1 is a schematic diagram of a cross-sectional image of a particle of the first carbon-based material 100 of the present application. Figure 1 As shown, the region extending 2.5 μm from the particle surface of the first carbon-based material 100 to the inside of the particle is the outer region 101 , and the region inside the outer region 101 is the inner region 102 .
[0073] In the present application, the pore area, S1, and S2 values of the first carbon-based material can be obtained by using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher from Japan's JEOL company) to obtain the cross-section of the first carbon-based material; then, referring to JY / T010-1996, a scanning electron microscope (such as the Sigma300 scanning electron microscope from Germany's ZEISS company) is used to scan the cross-section of the first carbon-based material; finally, the pore area of any one hole in the first carbon-based material is obtained by image processing software (such as AVIZO); as well as the total pore area S2 of the internal region and the total pore area S1 of the external region, and thereby the value of S2 / S1 is obtained. Exemplarily, samples can be obtained from different regions of the negative electrode sheet in the secondary battery, and at least 5 positions (such as 5, 10, 15 or even more) are randomly selected from the sample to obtain cross sections using a cross-section polisher, and at least 10 particles (such as 10, 20, 50 or even more particles) are randomly selected from the scanning electron microscope images of each cross section. The total pore area S2' and the total pore area S1' of the inner region of each particle cross section are obtained by image processing software according to the above definition, and the S2' / S1' value of each particle cross section is obtained. The arithmetic mean of S2' / S1' of all the measured particle cross sections is calculated as the S2 / S1 value of the first carbon-based material.
[0074] In some embodiments, the area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 . The inventors also found in further research that by controlling the area of the pore structure in the outer region of the first carbon-based material within the above range, the outer region of the first carbon-based material can have a dense structure, thereby effectively improving the structural stability of the first carbon-based material and avoiding the electrolyte from penetrating into the pore structure inside the first carbon-based material particles as much as possible, thereby effectively improving the cycle performance of the secondary battery. Of course, the present application does not intend to limit the area of all pore structures in the outer region of the first carbon-based material to be less than or equal to 0.15 μm2 For example, the area of the pore structure can be controlled to be less than or equal to 0.15 μm by more than 95%, and optionally more than 99%. 2 .
[0075] In some embodiments, the inner region of the first carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of 0.15 μm 2 -2.0μm 2 The inventors also found in further research that by making the internal area of the first carbon-based material include a pore structure of the above size, on the one hand, sufficient and stable expansion space can be reserved for the volume change of the first carbon-based material particles, reducing the risk of crushing of the first carbon-based material particles and reducing the occurrence of side reactions; on the other hand, the compaction density of the negative electrode film layer can be increased to buffer the volume change of the negative electrode film layer.
[0076] In some embodiments, at least part of the surface of the first carbon-based material has a coating. Optionally, the coating includes a carbon coating. Optionally, more than 80% of the surface of the first carbon-based material is covered with a carbon coating, and further, 90%-100% of the surface of the first carbon-based material is covered with a carbon coating. In some embodiments, the carbon in the coating includes amorphous carbon and / or crystalline carbon with a degree of graphitization between 68% and 90%. Thus, by having a coating on at least part of the surface of the first carbon-based material, the kinetic performance of the secondary battery can be further improved.
[0077] In some embodiments, the gram capacity of the first carbon-based material is greater than or equal to 355 mAh / g, and can be 355 mAh / g-370 mAh / g, thereby further improving the energy density of the secondary battery.
[0078] In some embodiments, the actual density of the first carbon-based material is 2.22 g / cm 3 -2.27g / cm 3 , optional 2.23g / cm 3 -2.26g / cm 3 When the true density of the first carbon-based material is within the above range, it is beneficial to improve the compaction density of the negative electrode film layer and further improve the energy density of the secondary battery.
[0079] In some embodiments, the powder compaction density of the first carbon-based material under a pressure of 20000N is 1.65g / cm 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3When the compaction density of the first carbon-based material powder is within the above range, the compaction density of the negative electrode film layer can be increased, and the energy density of the secondary battery can be increased; it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transmission performance, and improve the infiltration and retention characteristics of the negative electrode film layer to the electrolyte, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0080] In some embodiments, the volume distribution particle size Dv50 of the above-mentioned first carbon-based material is 8.0μm-25.0μm, and can be optionally 10.0μm-22.0μm. In some embodiments, the volume distribution particle size Dv90 of the above-mentioned first carbon-based material is 16.0μm-45.0μm, and can be optionally 16.5μm-42.0μm. When the volume distribution particle size Dv50 and / or Dv90 of the first carbon-based material is within the above range, it is beneficial to improve the transmission performance of active ions and electrons, thereby further improving the kinetic performance of the secondary battery. In addition, it can also reduce the specific surface area of the first carbon-based material, reduce the occurrence of side reactions, and improve the cycle performance of the secondary battery.
[0081] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is less than or equal to 1.55, and can be optionally 0.90-1.50. When the particle size distribution (Dv90-Dv10) / Dv50 of the first carbon-based material is within the above range, its particle stacking performance is good, which is conducive to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery; in addition, it is also conducive to adjusting the pore distribution of the negative electrode film layer, improving the active ion and electron transport performance, and improving the infiltration and retention characteristics of the negative electrode film layer to the electrolyte, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0082] In some embodiments, the tap density of the first carbon-based material is 0.85 g / cm 3 -1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 When the tap density of the first carbon-based material is within the above range, it has good processing performance, and can also increase the compaction density of the negative electrode film layer and the energy density of the secondary battery.
[0083] In some embodiments, the adsorption amount of linseed oil by 100g of the first carbon-based material is 30mL-47mL. When the adsorption amount of linseed oil by the carbon material is within the above range, the first carbon-based material has better processing performance and the surface side reaction activity of the particles is lower, thereby reducing the consumption of active ions by SEI film formation.
[0084] In some embodiments, the first carbon-based material D / I G Less than or equal to 0.280, and can be 0.155-0.220. Thus, the active lithium consumption can be effectively reduced, the cycle performance can be further improved, and the kinetic performance can be taken into consideration at the same time.
[0085] In some embodiments, the gram capacity of the second carbon-based material is 280mAh / g-340mAh / g, which can be 300mAh / g-338mAh / g. As a result, it is beneficial to improve the kinetic performance of the secondary battery. In some embodiments, the interlayer spacing of the 002 crystal plane of the second carbon-based material is 0.33622nm-0.33669nm, which can be 0.33626nm-0.33665nm. By adjusting the interlayer spacing of the second carbon-based material within the above range, it is beneficial to the rapid deintercalation of active ions, which is beneficial to improving the active ion transport performance of the negative electrode film layer, thereby further improving the kinetic performance of the secondary battery.
[0086] In some embodiments, the volume distribution particle size Dv50 of the second carbon-based material is 10 μm-18 μm, and can be 12 μm-17 μm. By making the volume distribution particle size Dv50 of the second carbon-based material within the above range, the specific surface area of the second carbon-based material can be reduced, the occurrence of side reactions can be reduced, and the cycle performance of the secondary battery can be improved.
[0087] In some embodiments, the tap density of the second carbon-based material is 0.95 g / cm 3 -1.35g / cm 3 , optional 1.00g / cm 3 -1.30g / cm 3 By making the tap density of the second carbon-based material within the above range, the second carbon-based material has better processing performance, and at the same time, the compaction density of the negative electrode film layer can be increased, thereby increasing the energy density of the secondary battery.
[0088] In some embodiments, the volume distribution particle size Dv90 of the second carbon-based material is 25.0 μm-45.0 μm, and can be 26.5 μm-42.0 μm. The second carbon-based material has good processing performance and is conducive to having a suitable pore distribution in the negative electrode film layer, thereby improving the dynamic performance of the secondary battery.
[0089] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second carbon-based material is less than or equal to 1.90, and can be selected as 0.90-1.85. This is beneficial to improving the compaction density of the negative electrode film layer and the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transmission performance in the negative electrode film layer, and thus improve the kinetic performance of the secondary battery.
[0090] In some embodiments, the adsorption amount of linseed oil by 100g of the second carbon-based material is 38mL-50mL. When the adsorption amount of linseed oil by the carbon material is within the above range, the processing performance of the second carbon-based material particles is better and the surface side reaction activity is lower, thereby reducing the consumption of active ions by SEI film formation.
[0091] In some embodiments, the content of the first carbon-based material in the negative electrode active material is greater than or equal to 30%, and can be 50wt%-80wt%, for example, 55wt%-75wt%, 60wt%-70wt%. The content of the second carbon-based material in the negative electrode active material is less than or equal to 70%, for example, 20wt%-50wt%, and can be 25wt%-45wt%, 30wt%-40wt%. When the contents of the first carbon-based material and the second carbon-based material are respectively within the above ranges, the secondary battery can take into account high energy density, good kinetic performance and cycle performance.
[0092] Optionally, the second carbon-based material includes artificial graphite, which generally refers to crystalline carbon obtained by high-temperature graphitization treatment, and usually does not have a pore structure inside, or does not have a pore structure that can be directly observed from a cross-sectional image (such as a scanning electron microscope image with a magnification of 1000 times).
[0093] In some embodiments, the second carbon-based material D / I G The ratio is 0.20-0.40, and can be 0.25-0.35, thereby further improving the dynamic performance.
[0094] In some embodiments, the negative electrode active material may further include other negative electrode active materials known in the art in addition to the first carbon-based material and the second carbon-based material. For example, the negative electrode active material may also include a silicon-based material. The higher lithium insertion potential of the silicon-based material helps to improve the kinetic performance of the secondary battery; at the same time, it can also improve the negative electrode capacity, thereby further improving the energy density of the secondary battery. Optionally, the silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material.
[0095] In some embodiments, when the negative electrode active material in the negative electrode film layer further includes a silicon-based material, the content of the silicon-based material is 0.5wt%-30wt%, for example, 0.8%-25%, 1%-20%, 1%-15%, 1%-10%, 1.5%-8%, 2%-6%, or 3%-7%. This can improve the kinetic performance and energy density of the secondary battery while giving the secondary battery good cycle performance and cycle performance.
[0096] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0097] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0099] In some embodiments, the compaction density of the negative electrode film is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3 -1.85g / cm 3 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good cycle performance and kinetic performance.
[0100] In some embodiments, the surface density of the negative electrode film is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 This is beneficial for the negative electrode film layer to have both high capacity and high active ion and electron transport performance, and further beneficial for the secondary battery to have both high energy density and good cycle performance and kinetic performance.
[0101] In some embodiments, the thickness of the negative electrode film layer is 40 μm-120 μm, and optionally 45 μm-100 μm.
[0102] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0103] The negative electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector. It should be noted that the parameters of the negative electrode film layer (such as compaction density, surface density, thickness, etc.) given in this application refer to the parameters of the negative electrode film layer on one side of the negative electrode current collector. When the negative electrode film layer is arranged on both sides of the negative electrode current collector, the parameters of the negative electrode film layer on either side meet the requirements of this application, which is considered to fall within the protection scope of this application.
[0104] In the present application, the negative electrode sheet may include other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode sheet also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet also includes a protective layer covering the surface of the negative electrode film layer.
[0105] In the present application, the graphitization degree of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the crystal structure of the material. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0106] In the present application, the interlayer spacing of the 002 crystal plane of the material (e.g., the first carbon-based material, the second carbon-based material) is a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (e.g., Bruker D8 Discover) can be used for testing, and the test can refer to JIS K0131-1996 and JB / T 4220-2011 to obtain the interlayer spacing of the C (002) crystal plane in the crystal structure of the material.
[0107] In the present application, the gram capacity of materials (such as the first carbon-based material, the second carbon-based material, etc.) has a well-known meaning in the art and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol / L The electrolyte was then used as a counter electrode and a polyethylene (PE) film as an isolation membrane, and the above electrolyte was assembled into a CR2430 button cell in an argon-protected glove box; the button cell was left to stand for 12 hours, and then discharged at 0.05C constant current to 0.005V at 25°C, left to stand for 10 minutes, and then discharged at 50μA constant current to 0.005V, left to stand for 10 minutes, and then discharged at 10μA constant current to 0.005V; then charged at 0.1C constant current to 2V, and the charge capacity was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (e.g., the first carbon-based material, the second carbon-based material, etc.).
[0108] In the present application, the first carbon-based material and the second carbon-based material I D / I G Raman spectrometer can be used for testing. D The Raman spectrum of the material is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of the material is 1580±50cm -1 The test conditions are: excitation wavelength of 532nm, grating of 600 lines, objective lens of 50 times, integration time of 10s, accumulation times of 3 times, surface scanning, obtain the D peak and G peak intensity of 100 points, calculate the I of 100 points D / I G , remove the largest and smallest 30 I D / I GThe average value of the remaining 40 points is the I D / I G The testing instrument may be a Horiba LabRAM HR800 Raman spectrometer.
[0109] In the present application, whether there is a coating layer on the surface of a material (eg, the first carbon-based material, the second carbon-based material, etc.) can be determined by transmission electron microscopy.
[0110] In the present application, the true density of a material (such as a first carbon-based material, a second carbon-based material, etc.) has a meaning well known in the art and can be tested using methods known in the art. Referring to standard GB / T24586-2009, an exemplary test method is as follows: Take a clean and dry sample cup and place it on a balance, reset it to zero, add the powder sample to the sample cup, which occupies about 1 / 2 of the volume of the sample cup, and record the mass of the sample. Place the sample cup containing the sample in a true density tester, a closed test system, and helium gas according to the procedure. By detecting the pressure of the gas in the sample chamber and the expansion chamber, the true volume is calculated according to Bohr's law (PV=nRT), thereby calculating the true density. Test sample cup volume: 3.5cm 3 , analysis gas: helium.
[0111] In this application, the volume distribution particle sizes Dv10, Dv50, and Dv90 of materials (such as the first carbon-based material, the second carbon-based material, etc.) are well-known in the art, which respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0112] In the present application, the powder compaction density of a material (e.g., the first carbon-based material, the second carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (e.g., a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. An exemplary test method is as follows: Weigh 1 g of sample powder and add a bottom area of 1.327 cm 2 The mold is pressurized to 2000kg, maintained for 30s, then released and maintained for 10s, and then the powder compaction density of the material under a pressure of 20000N is recorded and calculated.
[0113] In the present application, the tap density of a material (e.g., a first carbon-based material, a second carbon-based material, etc.) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, GB / T 5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0114] In this application, the adsorption amount of linseed oil by 100g of the first carbon-based material can be tested according to the following method: Referring to GB / T 3780.2-2017, weigh a certain mass (for example, 20g) of the dried test sample, place the weighed sample in the mixing chamber of the oil absorption meter, the temperature of the mixing chamber is 22℃-23℃, and cover the lid; align the oil delivery pipe of the constant-speed burette with the top of the hole in the mixing chamber cover; start the oil absorption meter, the instrument starts to run and linseed oil is added dropwise. As the oil absorption of the sample increases, the mixed material changes from a free-flowing state to a semi-plastic agglomerate, and the viscosity of the mixture continues to increase. The viscosity is transmitted to the torque sensor system of the oil absorption meter. When the added oil makes the semi-plastic agglomerate reach the preset torque level, the oil absorption meter and the constant-speed burette are automatically closed; read the value corresponding to 70% of the maximum torque of the fitting curve, and use the formula A=(V / m)×100 to calculate the adsorption amount A of 100g of carbon material on linseed oil, where V represents the volume of linseed oil consumed by the sample corresponding to 70% of the maximum torque, in ml; m is the mass of the added sample, in g.
[0115] In the present application, primary particles have a meaning known in the art. Primary particles refer to non-agglomerated particles, and particles aggregated from primary particles are secondary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0116] In the present application, the number ratio of primary particles in the first carbon-based material and / or the second carbon-based material refers to: randomly selecting a test sample in the negative electrode film layer, randomly selecting multiple test areas in the test sample, using a scanning electron microscope to obtain images of the multiple test areas, and counting the number of first carbon-based materials with primary particle morphology in each image as a ratio of the total number of first carbon-based material particles. The average value of multiple statistical results is the number ratio of primary particles in the first carbon-based material.
[0117] In this application, the surface density of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art. For example, a negative electrode sheet coated on one side and cold pressed can be taken (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punched into small discs with an area of S1, weighed, and recorded as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. Surface density of negative electrode sheet = (M1-M0) / S1.
[0118] In the present application, the compaction density of the negative electrode film layer is a well-known meaning in the art and can be tested by methods known in the art. The compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer is a well-known meaning in the art and can be tested by methods known in the art, such as using a micrometer (e.g., Mitutoyo 293-100, with an accuracy of 0.1 μm).
[0119] It should be noted that the above-mentioned various parameter tests on the negative electrode active material or the negative electrode film layer can be conducted by sampling and testing from the prepared secondary battery according to the following steps.
[0120] Discharge the secondary battery (for safety reasons, the secondary battery is generally fully discharged); disassemble the secondary battery and take out the negative electrode sheet, and soak the negative electrode sheet in dimethyl carbonate for a certain period of time (e.g., 2h-10h); then take out the negative electrode sheet and dry it at a certain temperature and time (e.g., 60°C, more than 4h), and take out the negative electrode sheet after drying. At this time, you can take samples from the dried negative electrode sheet to test the above-mentioned parameters related to the negative electrode film, such as the surface density, compaction density, thickness, etc. of the negative electrode film.
[0121] The dried negative electrode sheet is baked at a certain temperature and time (for example, 400°C for more than 2h), and a region of the baked negative electrode sheet is selected to sample the negative electrode active material (a blade can be used to scrape the powder for sampling); the collected negative electrode active material is sieved (for example, sieved with a 200-mesh sieve), and finally a sample that can be used to test the parameters of the above-mentioned negative electrode active materials is obtained.
[0122] The first carbon-based material and the second carbon-based material can be distinguished by a cross-section polisher. For example, the types of the first carbon-based material and the second carbon-based material can be distinguished by performing an ion polishing cross-sectional morphology (CP) test on the negative electrode piece. As an example, the test method can be: cut the negative electrode piece into a sample to be tested of a certain size (for example, 2cm×2cm), and use paraffin to fix the negative electrode piece on the sample stage; put the sample stage into the sample holder and lock it, turn on the power of the argon ion cross-section polisher (for example, the IB-09010CP argon ion cross-section polisher of Japan's JEOL) and evacuate (for example, 10-4 Pa), set the argon gas flow rate (e.g., 0.15MPa) and voltage (e.g., 8KV) and polishing time (e.g., 2h), adjust the sample stage to the swing mode and start polishing; randomly select an area in the sample to be tested for scanning test (e.g., refer to JY / T010-1996, use a scanning electron microscope for scanning), and obtain an ion polishing cross-sectional morphology (CP) image of the negative electrode piece at a certain magnification (e.g., 1000 times), from which the first carbon-based material and the second carbon-based material can be distinguished.
[0123] In the present application, the second carbon-based material can be obtained commercially and can be prepared by a known method. In addition, the first carbon-based material can be prepared by the following method of the present application.
[0124] In some embodiments, the preparation method of the above-mentioned first carbon-based material includes: step 1, providing a raw material with a plurality of pore structures; step 2, mixing the above-mentioned raw material and the filling material evenly in a predetermined proportion, and then keeping it warm at a first temperature T1 for a first time t1, and cooling to room temperature to obtain an intermediate after the end; step 3, keeping the obtained intermediate warm at a second temperature T2 for a second time t2, and obtaining the first carbon-based material after the end.
[0125] In some embodiments, in step 1, the raw material used to prepare the first carbon-based material includes natural graphite. Natural graphite generally refers to graphite formed naturally in nature and does not need to be graphitized. Optionally, the natural graphite includes one or more of flake graphite, natural spherical graphite and microcrystalline graphite, and more optionally includes natural spherical graphite.
[0126] "Natural spherical graphite" refers to natural graphite with a spherical or quasi-spherical shape, and not all natural graphite particles are controlled to be ideal spheres. In some embodiments, natural spherical graphite with a desired particle size and morphology can be obtained by pre-treating flake graphite, and optionally, the pre-treatment includes crushing, classification, spheroidization, purification and other processes.
[0127] In some embodiments, in step 1, the volume distribution particle size Dv50 of the raw material may be 6.0 μm-25.0 μm.
[0128] In some embodiments, in step 1, the specific surface area of the raw material may be ≥ 2.5 m 2 / g, optional 2.5m 2 / g-10.0m 2 When the specific surface area of the raw material is within the above range, it is beneficial to carry out subsequent filling treatment and obtain the first carbon-based material with the required specific surface area, and it is also beneficial for the first carbon-based material to have both high capacity and high first coulombic efficiency. In addition, it is also beneficial for the first carbon-based material to have better kinetic properties.
[0129] In some embodiments, in step 2, the softening point temperature of the filling material is 90°C-150°C. Optionally, the softening point temperature of the filling material is 94°C-146°C, 94°C-142°C, 94°C-138°C, 94°C-134°C, 94°C-130°C, 104°C-146°C, 104°C-142°C, 104°C-138°C, 104°C-134°C, 104°C-130°C.
[0130] In some embodiments, in step 2, the volume distribution particle size Dv50 of the filler material is less than or equal to 6 μm, and can be 1 μm-6 μm, 1 μm-5 μm, 2 μm-5 μm, 3 μm-5 μm. This is conducive to the filler material being melted by heat and filling into the pore structure of the raw material, and is also conducive to improving the dispersion uniformity of the filler material and the raw material.
[0131] In some embodiments, in step 2, the coking value of the filler material is 15%-40%, and can be 18%-34%. In the present application, the coking value of the filler material is a well-known meaning in the art, and can be measured by instruments and methods known in the art. For example, it can be measured with reference to GB / T 8727-2008.
[0132] In some embodiments, in step 2, the filling material includes one or more of coal tar, petroleum asphalt, polymer compounds and resins, and may optionally include one or more of coal tar and petroleum asphalt.
[0133] In some embodiments, in step 2, the mass ratio of the filler material to the raw material is (10-40):100, and may be (10-30):100, (10-25):100, (10-20):100, (12-30):100, (14-28):100, (15-25):100. Generally, when other process conditions remain unchanged, the more the filler material is added, the higher the carbon-based material I D / I G The larger the mass ratio, the greater the value. Those skilled in the art can adjust the mass ratio within the above-mentioned range according to their needs to obtain the desired I D / I G Numeric value.
[0134] In step 2, by adjusting one or more parameters such as the type, softening point, coking value, and addition amount of the filling material within the above-mentioned range, it is helpful to adjust the number and / or pore size of pores in the outer and inner regions of the first carbon-based material within a suitable range, which is helpful to adjust the S2 / S1 of the first carbon-based material within a suitable range.
[0135] By adjusting the type, softening point, coking value, addition amount and other parameters of the filling material within the above range, the viscosity of the filling material is not high after it is heated and melted, and it maintains good fluidity. At the same time, it is not easy to adhere to the raw material particles, which can reduce the agglomeration of the raw material particles in the subsequent preparation process. This can also reduce the problems of increased surface defects of the first carbon-based material particles and increased surface active sites due to the need to add a depolymerization step.
[0136] In some embodiments, in step 2, the heating process of uniformly mixing the raw material and the filling material in a predetermined ratio and then heating the mixture to the first temperature T1 may be a staged heating process.
[0137] In some embodiments, the phased temperature increasing process includes a first temperature increasing process, a second temperature increasing process, and a third temperature increasing process.
[0138] In some embodiments, the first temperature rising process is to raise the temperature to 200° C.-250° C. and keep the temperature at this temperature for 0.5 h-3 h.
[0139] In some embodiments, the second temperature increase process is to increase the temperature to 450°C-550°C and keep the temperature at this temperature for 0h-2h. When the holding time is 0h, it means that when the temperature is increased to the range of 450°C-550°C, no holding treatment is performed, but the temperature continues to be increased to the first temperature T1.
[0140] In some embodiments, the third temperature increasing process is to increase the temperature to the first temperature T1 and keep the temperature at the first time t1.
[0141] In the staged heating process, the temperature is first raised to 200℃-250℃. Since the heating temperature is higher than the softening point of the filling material, the filling material is melted and softened by the heat. Keeping it warm for 0.5h-3h allows it to flow and fill into the pore structure of the raw material; then the temperature is raised to 450℃-550℃. At this time, the melted and softened filling material undergoes a carbonization reaction, gradually forming a semi-coke state and turning into a viscous liquid or solid, thereby preventing the filling material from entering the entire pore structure of the raw material; finally, the temperature is raised to the first temperature. At this time, the filling material undergoes a carbonization reaction, thereby enabling the pore structure occupied by the filling material to be effectively filled.
[0142] In some embodiments, in step 2, the temperature is raised to the first temperature T1 at a rate of 1°C / min-10°C / min. For example, the heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any range thereof. Optionally, the heating rate is 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, 2°C / min-5°C / min.
[0143] In some embodiments, the heating rate of the first heating process may be 1°C / min-10°C / min, and may be 1.5°C / min-8°C / min, 1.5°C / min-6°C / min, 2°C / min-6°C / min, or 2°C / min-5°C / min. In some embodiments, the heating rate of the second heating process may be 1°C / min-10°C / min, and may be 2°C / min-8°C / min. In some embodiments, the heating rate of the third heating process may be 1°C / min-10°C / min, and may be 2°C / min-8°C / min.
[0144] In some embodiments, in step 2, the first temperature T1 is 700°C-1200°C. For example, the first temperature T1 can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1200°C or any range thereof. Optionally, the first temperature T1 is 750°C-1100°C, 800°C-1100°C, 850°C-1100°C, 900°C-1100°C, 850°C-1000°C.
[0145] In some embodiments, in step 2, the first time t1 is 1 hour to 5 hours. For example, the first time t1 can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours or any range thereof. Optionally, the first time t1 is 2 hours to 4 hours.
[0146] In some embodiments, in step 2, the heat treatment can be carried out in a medium frequency furnace, a roller kiln, a rotary kiln, a push plate kiln, a vertical granulation kettle, a horizontal granulation kettle, a vertical reactor, a horizontal reactor or a drum furnace, etc., which can perform programmed temperature increase.
[0147] In some embodiments, in step 2, the heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.
[0148] In step 2, by adjusting one or more of the heating rate, the first temperature, the first time, the heating process, etc. within the above-mentioned range, it is helpful to adjust the number of pores and / or the pore size in the outer region and the inner region of the first carbon-based material within a suitable range, and then it is helpful to adjust the S2 / S1 of the first carbon-based material within a suitable range.
[0149] In some embodiments, in step 3, the second temperature T2 is 2070° C.-2700° C. Optionally, the second temperature T2 is 2070° C.-2570° C., 2070° C.-2510° C., 2070° C.-2450° C., 2070° C.-2360° C., 2140° C.-2570° C., 2140° C.-2510° C., 2140° C.-2450° C., 2140° C.-2360° C.
[0150] In some embodiments, in step 3, the second time t2 is 1.5h-6h. For example, the second time t1 can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h or any range thereof. Optionally, the second time t2 is 2h-5h.
[0151] In some embodiments, in step 3, the heat treatment may be performed in a medium frequency furnace, a box-type graphitization furnace, an Acheson graphitization furnace, a continuous graphitization furnace, or an inner-string graphitization furnace.
[0152] In some embodiments, in step 3, the medium frequency furnace and the continuous graphitization heat treatment atmosphere may be a protective gas atmosphere. The protective gas may include one or more of nitrogen, argon, and helium.
[0153] In step 3, by adjusting one or more of the second temperature and the second time within the above range, it is beneficial to adjust the content of disordered carbon in the first carbon-based material within a suitable range, which is beneficial for the first carbon-based material to have a suitable graphitization degree, interlayer spacing and I D / I G In general, when other process conditions remain unchanged, the higher the second temperature, the higher the I of the first carbon material. D / I G The smaller the temperature, the smaller the temperature. Those skilled in the art can adjust the temperature within the above-mentioned temperature range according to their needs to obtain the required I D / I G Numeric value.
[0154] In the preparation method of the above-mentioned first carbon-based material, by adjusting one or more of the parameters of natural graphite, the parameters of the filling material, the heating rate, the first temperature, the first time, the heating process, the second temperature, the second time, etc. within the above-mentioned range, it is beneficial to adjust the parameters of the first carbon-based material such as S2 / S1, graphitization degree, gram capacity, particle size, powder compaction density, tap density, and adsorption amount of linseed oil.
[0155] In some embodiments, the first carbon-based material obtained above is mixed with an organic carbon source and then carbonized to form a carbon coating layer on at least a portion of the surface of the particles. Optionally, the organic carbon source may be a carbon-containing material known in the art suitable for coating, for example, one or more of coal tar, petroleum asphalt, phenolic resin, coconut shell, etc. Optionally, the carbonization temperature is 900°C-1300°C.
[0156] In some embodiments, the preparation method of the above-mentioned second carbon-based material includes: step 11, providing raw materials; step 12, crushing and shaping the raw materials to obtain a first intermediate; step 13, graphitizing the first intermediate to obtain the second carbon-based material.
[0157] In some embodiments, in step 11, the feedstock may include one or more of petroleum coke, needle coke, pitch coke, and metallurgical coke.
[0158] In some embodiments, in step 12, a mechanical mill or a roller mill may be used to crush the raw material. In addition, a shaping machine may be used for shaping.
[0159] In some embodiments, in step 13, the graphitization temperature is 2700°C-3200°C.
[0160] By adjusting the graphitization temperature and / or the graphitization time, the second carbon-based material can have a suitable graphitization degree. In the above-mentioned method for preparing the second carbon-based material, by adjusting one or more parameters of the raw material parameters (such as particle size, particle size distribution, gram capacity, etc.), it is beneficial to adjust the graphitization degree, interlayer spacing, gram capacity, particle size, tap density and other parameters of the second carbon-based material.
[0161] [Positive electrode]
[0162] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0163] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0164] The positive electrode film layer generally comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is generally formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0165] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.
[0166] When the secondary battery of the present application is a lithium-ion battery, the above-mentioned positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the above-mentioned lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the above-mentioned lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0167] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Coc M d O e A f One or more of lithium transition metal oxides and their modified compounds thereof. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.
[0168] In some embodiments, by way of example, the positive electrode active material for a lithium ion battery may include one or more of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, and LiMnPO4.
[0169] In the present application, the modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the above positive electrode active materials.
[0170] [Electrolyte]
[0171] In some embodiments, the above electrolyte uses an electrolytic solution, and the above electrolytic solution includes an electrolyte salt and a solvent.
[0172] The types of the above electrolyte salts are not specifically limited and can be selected according to actual needs.
[0173] When the secondary battery of the present application is a lithium ion battery, as an example, the above-mentioned electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0174] The types of the above-mentioned solvents are not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the above-mentioned solvents may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0175] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.
[0176] [Isolation film]
[0177] The present application has no particular limitation on the type of the above-mentioned isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0178] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0179] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet can be made into an electrode assembly by a winding process or a lamination process.
[0180] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte.
[0181] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the above soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0182] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.
[0183] In some embodiments, Figure 3 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the above opening to close the above receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the above receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0184] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0185] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0186] Figure 4 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 4 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0187] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0188] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0189] Figure 5 and Figure 6 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0190] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0191] The above-mentioned electrical devices can select secondary batteries, battery modules or battery packs according to their usage requirements.
[0192] Figure 7 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0193] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0194] Example
[0195] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0196] Preparation of the first carbon-based material:
[0197] Materials 1-1
[0198] Step 1, mechanically crush, classify, spheroidize and purify the flake graphite to obtain natural spherical graphite. Step 2, mix the obtained natural spherical graphite with the filler petroleum asphalt in a mass ratio of 100:23, the softening point of the petroleum asphalt is 120°C, and the coking value is 36%. Then place the mixed material in a programmable temperature rising device, heat it to 200°C and keep it warm for 1 hour (the first heating process), and then continue to heat it to 700°C and keep it warm for 2 hours (the third heating process). After the end, cool it to room temperature to obtain an intermediate. Step 3, place the obtained intermediate in a graphitization furnace and perform a heat treatment at 2250°C. After the end, demagnetize and screen it to obtain the first carbon-based material (material 1-1). The obtained material 1-1 meets the following requirements: S2 / S1 is 11.6, the degree of graphitization is 94.9%, I D / I G It is 0.175, and the number of primary particles accounts for 80%.
[0199] The S2 / S1 of the first carbon-based material is obtained by testing using the following method.
[0200] The sample preparation binder and the first carbon-based material powder are mixed evenly and then applied to the copper foil, dried at 60°C for 30 minutes for use; 5 samples to be tested are cut into 6mm×6mm sizes at 5 different positions and pasted on the sample stage of the CP type argon ion cross-section polisher respectively; the samples are cut using a plasma beam to obtain the cross section of each sample. The test instrument can be the IB-09010CP type argon ion cross-section polisher of Japan JEOL Company.
[0201] The cross sections of each sample of the first carbon-based material are scanned using a scanning electron microscope, and a scanned image is obtained by arbitrarily selecting an area in each cross section of the sample. The test may refer to JY / T010-1996. The test instrument may be a Sigma 300 scanning electron microscope from the German ZEISS company.
[0202] Randomly select cross sections of 20 particles of the first carbon-based material from the scanned image. The area formed by extending 0.25 μm from the particle surface of the first carbon-based material to the inside of the particle is recorded as the external area, and the area inside the external area is recorded as the internal area. Use image processing software to obtain the total pore area S1' of the external area of each particle cross section and the pore area S2' of the internal area of the first carbon-based material, and calculate the value of S2' / S1'; and calculate the arithmetic mean of S2' / S1' of all 20 particles as the value of S2 / S1 of the first carbon-based material. The image processing software can be AVIZO.
[0203] Materials 1-2 to 1-4
[0204] The preparation methods of materials 1-2 to 1-4 are similar to those of material 1-1, except that the amounts of spherical graphite and filler and the heat treatment temperature are adjusted as shown in Table 1, so that the graphitization degrees of materials 1-2 to 1-4 are the values shown in Table 1. The details are as follows:
[0205] Table 1.
[0206]
[0207] Materials 1-5 to 1-9
[0208] The preparation methods of materials 1-5 to 1-9 are similar to those of material 1-1, except that the softening point temperature, coking value, and mixing ratio of natural spherical graphite and filler petroleum asphalt of the filler material are adjusted as shown in Table 2, and then the third heating process is adjusted so that the S2 / S1 of the first carbon-based material is the value shown in Table 2.
[0209] Table 2
[0210]
[0211] Materials 1'-1
[0212] The preparation method of material 1'-1 is similar to that of material 1-1, except that the material is adjusted as shown in Table 3 so that S2 / S1 of the first carbon-based material is the value shown in Table 3.
[0213] Table 3
[0214]
[0215] Materials 1-10 to 1-12
[0216] The preparation methods of materials 1-10 to 1-12 are similar to the preparation method of the above-mentioned material 1-1, except that the mixing ratio of natural spherical graphite and filler petroleum asphalt and the temperature of heat treatment are adjusted as shown in Table 4, so that I of the first carbon-based materialD / I G The values are as shown in Table 4.
[0217] Table 4
[0218]
[0219] In the following examples and comparative examples, the second carbon-based material was obtained through commercial purchase (purchased from Shanghai Shanshan Technology Co., Ltd. and Jiangxi Zichen Technology Co., Ltd.).
[0220] Example 1
[0221] Preparation of secondary batteries
[0222] 1. Negative electrode sheet: The negative electrode active material (material 1-1 (the first carbon-based material) and the second carbon-based material are mixed at a mass ratio of 70:30), conductive agent carbon black (Super P), thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.4:1:1.2:1.4 to form a negative electrode slurry. The negative electrode slurry is coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0223] 2. Positive electrode: LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) is mixed with conductive agent carbon black (Super P) and binder polyvinylidene fluoride in a weight ratio of 96:2:2, and an appropriate amount of solvent NMP is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0224] 3. Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0225] 4. Isolation film: Polypropylene film is used as isolation film.
[0226] 5. Secondary battery: Place the positive electrode sheet and negative electrode sheet prepared above in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain an electrode assembly; place the electrode assembly in an outer package, inject electrolyte after drying, and obtain a secondary battery after vacuum packaging, standing, forming, shaping and other processes.
[0227] Embodiments 2 to 10
[0228] The battery preparation methods of Examples 2-10 are similar to those of Example 1, except that the first carbon-based material or the second carbon-based material is a material with a different degree of graphitization, as shown in Table 5 for details.
[0229] Comparative Example 1
[0230] The preparation was performed in the same manner as in Example 1, except that Material 1-4 was used as the first carbon-based material, and the second carbon-based material was not used.
[0231] Comparative Example 2
[0232] The preparation was performed in the same manner as in Example 1 except that the first carbon-based material was not used.
[0233] Comparative Example 3
[0234] The preparation was performed in the same manner as in Example 1, except that Material 1-4 was used as the first carbon-based material and the graphitization degree of the second carbon-based material was greater than that of the first carbon-based material.
[0235] Comparative Example 4
[0236] The preparation was performed in the same manner as in Example 1 except that Material 1'-1 was used as the first carbon-based material.
[0237] Performance Testing
[0238] (1) Energy density
[0239] At 25°C, the secondary battery was charged to 4.3V at 1 / 3C constant current, then charged to 0.05C at 4.3V constant voltage, left to stand for 5 minutes, and then discharged to 2.8V at 1 / 3C constant current, and the battery discharge energy was recorded. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg. The measurement data is shown in Table 5.
[0240] (2) 1200cycle pole piece expansion rate
[0241] The thickness of the negative electrode after cold pressing is recorded as H0. The cold-pressed negative electrode sheet is made into a secondary battery with the positive electrode sheet, the isolation membrane, and the electrolyte. At 25°C, the secondary battery is subjected to a 1C / 1C cycle of 100% DOD (100% depth of discharge, that is, full charge and then full discharge) in a Xinwei charger and discharger. The discharge capacity of the first cycle (i.e., the initial capacity) is recorded as 100%, and the cycle stops when the cycle reaches 1200 cycles. Then charge the secondary battery to 100% SOC (State of Charge), disassemble the secondary battery and test the thickness of the corresponding negative electrode sheet, which is recorded as H1.
[0242] The cycle expansion rate of the negative electrode plate after 1200 cycles is: (H1 / H0-1)×100%.
[0243] (3) Cycle performance test of secondary batteries
[0244] At 45°C, the prepared secondary battery was charged at a constant current of 1C to an upper cut-off voltage (corresponding to 100% SOC), then charged at a constant voltage to a current of 0.05C, and after standing for 5 minutes, the secondary battery was discharged at a constant current of 1C to a lower cut-off voltage (corresponding to 0% SOC), and the discharge capacity at this time was recorded, which was the discharge capacity of the first cycle. The secondary battery was subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded.
[0245] Capacity retention rate of secondary battery after 1000 cycles at 45° C. (%)=discharge capacity after 1000 cycles / discharge capacity at the first cycle×100%.
[0246] (4) Secondary battery fast charging performance test
[0247] At 25°C, the secondary battery was charged to 4.3V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.8V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0248] Then the secondary battery is charged with constant current at 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0 in sequence to 4.3V or 0V negative electrode cut-off potential (whichever is reached first). After each charge, it is discharged to 2.8V at 1C0. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80%. The charging rate-negative electrode potential curve under different SOC states is drawn, and the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC respectively. The charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium) is calculated according to the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, and the unit is min.
[0249] The shorter the charging time is, the better the dynamic performance of the secondary battery is.
[0250] Table 5
[0251]
[0252] It can be seen from the results in Table 5 that in Examples 1 to 10, by making the negative electrode active material in the negative electrode film layer include a first carbon-based material whose S2 is greater than S1 and a second carbon-based material whose degree of graphitization is less than that of the first carbon-based material, the expansion of the electrode sheet can be effectively suppressed, and the secondary battery has excellent cycle performance and kinetic performance, and excellent energy density.
[0253] Comparative Example 1 only contains the first carbon-based material. Although the cyclability is good, the charging time is very long and the kinetic performance is poor. Comparative Example 2 only includes the second carbon-based material, which has a low degree of graphitization and a low energy density; the content of the amorphous carbon component is high. Although the expansion rate is low, due to the high activity of amorphous carbon, it is easy to react with the electrolyte, so the cyclability is poor. In Comparative Example 3, although the first carbon-based material and the second carbon-based material are included, the degree of graphitization of the second carbon-based material is higher than that of the first carbon-based material. Therefore, the pole piece has a high expansion rate and poor cyclability. In addition, the degree of graphitization is high and the interlayer spacing is small, resulting in a long charging time and poor kinetic performance. In Comparative Example 4, when S2 / S1 of the first carbon-based material is equal to 0.92, the cyclability is poor.
[0254] Examples 11-16
[0255] Except that S2 / S1 of the first carbon-based material was set to the value shown in Table 6, a battery was prepared in the same manner as in Example 4. The specific results are shown in Table 5.
[0256] Table 6
[0257]
[0258] From the results in Table 6, it can be seen that by setting 1.8≤S2 / S1≤199.8, the cycle performance and kinetic performance of the secondary battery are further improved, and by setting 2.3≤S2 / S1≤148.7, the cycle performance and kinetic performance of the secondary battery are further improved.
[0259] Examples 16-21
[0260] In addition to making the first carbon-based material and the second carbon-based material D / I G A secondary battery was prepared in the same manner as in Example 4 except that the values are shown in Table 7. Specific parameters and test results are shown in Table 7.
[0261] Table 7
[0262]
[0263] From the results in Table 7, it can be seen that compared with Example 21, the I of the second carbon-based material in Examples 16-20 is D / I G Greater than the I of the first carbon-based material D / I G , the cycle performance and kinetic performance of the secondary battery are further improved. In Examples 17-19, by making A / B in the range of 0.45-0.85, the cycle performance and kinetic performance of the secondary battery can be further improved.
[0264] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector and comprising a negative electrode active material, wherein: The negative electrode active material includes a first carbon-based material and a second carbon-based material, The first carbon-based material includes an external region and an internal region located inside the external region, wherein the external region refers to a region extending 2.5 μm from the particle surface of the first carbon-based material to the inside of the particle, and in a cross-sectional view of the first carbon-based material, the total pore area of the external region is denoted as S1, the total pore area of the internal region is denoted as S2, and S2>S1, and the degree of graphitization of the first carbon-based material is greater than that of the second carbon-based material.
2. The secondary battery according to claim 1, wherein The graphitization degree of the first carbon-based material is greater than or equal to 95.5%, and may be 95.5%-98.0%; and / or the graphitization degree of the second carbon-based material is 85%-90.5%, and may be 85.5%-90%.
3. The secondary battery according to claim 1 or 2, wherein: The gram capacity of the second carbon-based material is less than the gram capacity of the first carbon-based material.
4. The secondary battery according to any one of claims 1 to 3, wherein The interlayer spacing of the 002 crystal plane of the second carbon-based material is greater than the interlayer spacing of the 002 crystal plane of the first carbon-based material.
5. The secondary battery according to any one of claims 1 to 4, wherein The second carbon-based material I D / I G Greater than the I of the first carbon-based material D / I G , I D The Raman spectrum of carbon-based materials is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of carbon-based materials is 1580±50cm -1 The G peak intensity at Optionally, the first carbon-based material I D / I G Denoted as A, I of the second carbon-based material D / I G Let it be B, then the range of A / B is 0.45-0.
85.
6. The secondary battery according to any one of claims 1 to 5, wherein The first carbon-based material and / or the second carbon-based material comprises primary particles; Optionally, the amount of the primary particles in the first carbon-based material accounts for greater than or equal to 80%; Optionally, the number of the primary particles in the second carbon-based material accounts for greater than or equal to 80%.
7. The secondary battery according to any one of claims 1 to 6, wherein 1.8≤S2 / S1≤199.8, optionally, 2.3≤S2 / S1≤148.
7.
8. The secondary battery according to claim 7, wherein The area of the pore structure in the outer region of the first carbon-based material is less than or equal to 0.15 μm 2 , can be selected to be less than or equal to 0.13μm 2 and / or, The inner region of the first carbon-based material includes at least one area greater than or equal to 0.15 μm 2 The pore structure may include one or more pores with an area of 0.15 μm 2 -2.0μm 2 The pore structure.
9. The secondary battery according to any one of claims 1 to 8, wherein At least part of the surface of the first carbon-based material has a coating layer; optionally, the coating layer includes a carbon coating layer.
10. The secondary battery according to any one of claims 1 to 9, wherein The first carbon-based material satisfies at least one of the following conditions: (1) The gram capacity of the first carbon-based material is greater than or equal to 355 mAh / g, and can be 355 mAh / g-370 mAh / g; (2) The true density of the first carbon-based material is 2.22 g / cm 3 -2.27g / cm 3 , optional 2.23g / cm 3 -2.26g / cm 3 ; (3) The powder compaction density of the first carbon-based material under a pressure of 20000N is 1.65g / cm 3 -2.0g / cm 3 , optional 1.68g / cm 3 -1.98g / cm 3 ; (4) The volume distribution particle size Dv50 of the first carbon-based material is 8.0 μm-25.0 μm, and can be optionally 10.0 μm-22.0 μm; (5) The volume distribution particle size Dv90 of the first carbon-based material is 16.0 μm-45.0 μm, and can be optionally 16.5 μm-42.0 μm; (6) the particle size distribution of the first carbon-based material (Dv90-Dv10) / Dv50 is less than or equal to 1.55, and can be selected as 0.90-1.50; (7) The tap density of the first carbon-based material is 0.85 g / cm 3- 1.30g / cm 3 , optional 0.90g / cm 3 -1.25g / cm 3 ; (8) The adsorption amount of linseed oil by 100g of the first carbon-based material is 30mL-47mL; (9) I of the first carbon-based material D / I G Less than or equal to 0.280, optional: 0.155-0.
220.
11. The secondary battery according to any one of claims 1 to 10, wherein The second carbon-based material satisfies at least one of the following conditions: (1) The gram capacity of the second carbon-based material is 280 mAh / g-340 mAh / g, and can be 300 mAh / g-338 mAh / g; (2) The interlayer spacing of the 002 crystal plane of the second carbon-based material is 0.33622nm-0.33669nm, and can be optionally 0.33626nm-0.33665nm; (3) the volume distribution particle size Dv50 of the second carbon-based material is 10 μm-18 μm, and can be optionally 12 μm-17 μm; (4) The tap density of the second carbon-based material is 0.95 g / cm 3 -1.35g / cm 3 , optional 1.00g / cm 3 -1.30g / cm 3 ; (5) The volume distribution particle size Dv90 of the second carbon-based material is 25.0 μm-45.0 μm, and can be optionally 26.5 μm-42.0 μm; (6) the particle size distribution of the second carbon-based material (Dv90-Dv10) / Dv50 is less than or equal to 1.90, and can be selected from 0.90 to 1.85; (7) The adsorption amount of linseed oil by 100g of the second carbon-based material is 38mL-50mL; (8) The second carbon-based material is artificial graphite; (9) I of the second carbon-based material D / I G It is 0.20-0.40, and can be optionally 0.25-0.
35.
12. The secondary battery according to any one of claims 1 to 11, wherein In the negative electrode active material, the content of the first carbon-based material is greater than or equal to 30 wt %, and can be optionally 50 wt %-80 wt %.
13. The secondary battery according to any one of claims 1 to 12, wherein The negative electrode active material further comprises a silicon-based material; optionally, in the negative electrode active material, the content of the silicon-based material is 0.5wt%-30wt%.
14. The secondary battery according to any one of claims 1 to 13, wherein The negative electrode film layer satisfies at least one of the following (1)-(3): (1) The compaction density of the negative electrode film layer is 1.45 g / cm 3 -1.90g / cm 3 , optional 1.50g / cm 3 -1.85g / cm 3 ; (2) The surface density of the negative electrode film layer is 5.0 mg / cm 2 -25.0mg / cm 2 , optional 5.5mg / cm 2 -22.5mg / cm 2 ; (3) The thickness of the negative electrode film layer is 40 μm-120 μm, and can be optionally 45 μm-100 μm.
15. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 14.
Citation Information
Patent Citations
Secondary battery
CN110148714A
Preparation method of negative electrode material for sodium ion battery
CN114709393A
Carbon material and a process for its manufacture
US20100035149A1
Cited By
Silicon-carbon composite material as well as preparation method and application thereof
CN120878791A
Negative electrode material and preparation method thereof, lithium ion battery and electric equipment
CN121439787A
Secondary battery and electric device
EP4819274A1